Growth of Ultrathin ZnCo2O4 Nanosheets on Reduced Graphene Oxide with Enhanced Lithium Storage Properties - Gao, Guoxin (2017)
The growth of ultrathin ZnCo2O4 nanosheets on reduced graphene oxide (denoted as rGO/ZnCo2O4) via a facile low-temperature solution method combined with a subsequent annealing treatment is reported. With the assistance of citrate, interconnected ZnCo2O4 nanosheets can assemble into hierarchically porous overlays on both sides of rGO sheets. Such a hybrid nanostructure would effectively faciliate the charge transport and accommodate volume variation upon prolonged charge/discharge cycling for reversible lithium storage. As a result, the rGO/ZnCo2O4 nanocomposite manifests a very stable high reversible capacity of around 960 mAh g−1 over 100 cycles at a low current density of 90 mA g−1 and excellent rate capability.